Kualitas mikrobiologi daging ayam broiler di pasar tradisional Banyumanik Semarang - Widayu Mutiya Ramadhani; Isworo Rukmi; Siti Nur Jannah (Jurnal Biologi Tropika, 2020)
Broiler chicken meat is a a kind of food that is easily spoilage due to bacterial growth. The chicken meat sold in the market could potentially become a medium of microbial growth of foodborne diseases. The aims of this research was to  determined the microbiological quality of chicken meat sold at traditional market in  Banyumanik, Semarang City and  examined the source of bacterial contaminant especially E. coli on chicken meat. Samples were taken from two markets in Banyumanik, namely Dm Market and Jt Market of Semarang. The samples were purposive taken, from two different sellers in each market. Sampling was conducted at 08.00 AM and 10.00 AM. The parameters in this study are the total number of bacteria, the number of E. coli and the presence of Salmonella sp.  The results showed that all samples examined did not meet the standard of good quality microbiological requirements for chicken meat according to SNI 3924:2009, regarding total bacteria, E. coli content and the presence of Salmonella sp. The results of observations by contact plate technique found that 50% of tools used by chicken meat sellers were contaminated by E. coli.